Penerimaan Keluarga pada Orang dengan HIV/AIDS (ODHA) - Choiriyah, Choiriyah; Pujianto, Ahmat; Ose, Maria Imaculata; Wahyudi, Donny Tri; Paridah, Paridah (Universitas Malahayati, 2024)
ABSTRACT HIV/AIDS is still being a problem that threatens the Indonesian people. The incidence rate in 2019 was 50,282 cases and it increased by 543,100 cases in 2022. People who are HIV positive, of course, will have problems both physically and psychologically. The problem that is currently being highlighted is family acceptance of people living with HIV/AIDS (PLWHA). Since the family is the first social environment that has an emotional attachment to one another, family support is a form of family acceptance of PLWHA. This research aimed to identify the description of family acceptance of people living with HIV/AIDS. Method: A descriptive quantitative research method with univariate analysis was employed on a sample sure of 105 respondents to describe the family acceptance. The result of the analysis showed that mean of the respondents had a low level of family acceptance. It could be concluded that PLWHA still got stigma and discrimination from that families. It is expected that health personal can be more active in providing education and socialization regarding HIV/AIDS and PLWHA to families and societer to reduce stigma and discrimination on order to improve the quality of life of PLWHA. Keywords: HIV/AIDS, PLWHA, Family Acceptance ABSTRAK HIV/AIDS masih menjadi masalah yang mengancam Indonesia. Angka kejadian tahun 2019 sebanyak 50.282 kasus dan tahun 2022 meningkat sebanyak 543.100 kasus. Bagi orang–orang yang divonis positif HIV, tentu akan memiliki masalah baik itu fisik, maupun psikologis. Permasalahan yang saat ini terus menerus disorot adalah penerimaan keluarga pada ODHA. Mengingat keluarga adalah lingkungan sosial pertama yang memiliki keterikatan emosional antar satu sama lain. Dukungan keluarga menjadi salah bentuk penerimaan keluarga terhadap ODHA. Sehingga penelitian ini bertujuan. Tujuan dari penelitian ini untuk mengidentifikasi gambaran penerimaan keluarga orang dengan HIV/AIDS (ODHA). Penelitian ini merupakan penelitian kuantitatif deskriptif yang melibatkan 105 responden. Hasil penelitian menunjukkan bahwa sebagian besar responden dengan tingkat penerimaan keluarga rendah. ODHA masih mendapatkan stigma dan diskriminasi dari keluarga. Diharapkan petugas kesehatan untuk lebih aktif dalam memberikan edukasi dan sosialisasi terkait HIV/AIDS dan ODHA kepada keluarga dan masyarakat umum untuk menurunkan angka stigma dan diskriminasi agar meningkatkan kualitas hidup ODHA. Kata Kunci: HIV/AIDS, ODHA, Penerimaan Keluarga